2015
DOI: 10.1074/jbc.m114.593806
|View full text |Cite
|
Sign up to set email alerts
|

Activatory and Inhibitory Fcγ Receptors Augment Rituximab-mediated Internalization of CD20 Independent of Signaling via the Cytoplasmic Domain

Abstract: Background: Fc␥ receptor (Fc␥R) IIb augments internalization of CD20 from the surface of B cells in response to rituximab treatment. Results: Activatory and inhibitory Fc␥R augment internalization, independent of the Fc␥R cytoplasmic domain. Conclusion: Active signaling is not required for Fc␥R-augmented internalization of CD20 in response to rituximab treatment. Significance: Fc␥R may play a structural role in augmenting CD20 internalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Recently, Stachowiak et al demonstrated that steric confinement of highly crowded protein within regions of artificial lipid membranes is enough to drive membrane puckering and lipid tubule formation in the membrane [37], observing that puckering increases with protein concentration. We have observed punctate staining of CD20 that colocalises with FcγRIIB upon ligation with type I anti-CD20 mAb, in contrast to diffuse staining observed with the non-redistributing type II mAb [18][19][20]29]. The high density redistribution of CD20 and FcγRIIB induced by type I anti-CD20 mAb-ligation resembles the high density staining observed in the artificial membranes generated by Stachowiak et al [37] and may therefore be sufficient to trigger membrane puckering and subsequent endocytosis.…”
Section: Role Of Lipid Raftssupporting
confidence: 47%
See 2 more Smart Citations
“…Recently, Stachowiak et al demonstrated that steric confinement of highly crowded protein within regions of artificial lipid membranes is enough to drive membrane puckering and lipid tubule formation in the membrane [37], observing that puckering increases with protein concentration. We have observed punctate staining of CD20 that colocalises with FcγRIIB upon ligation with type I anti-CD20 mAb, in contrast to diffuse staining observed with the non-redistributing type II mAb [18][19][20]29]. The high density redistribution of CD20 and FcγRIIB induced by type I anti-CD20 mAb-ligation resembles the high density staining observed in the artificial membranes generated by Stachowiak et al [37] and may therefore be sufficient to trigger membrane puckering and subsequent endocytosis.…”
Section: Role Of Lipid Raftssupporting
confidence: 47%
“…These data suggested that the interaction between type I anti-CD20 mAb and FcγRIIB may bring FcγRIIB and CD20 into close proximity in the plasma membrane, augmenting internalisation of the trimeric complex via phosphorylation of the FcγRIIB ITIM, analogous to the response with immune complex. However, investigations by Vaughan et al demonstrated that a truncated mutant form of FcγRIIB lacking the entire cytoplasmic domain was able to augment internalisation of type I anti-CD20 mAb-ligated CD20 as effectively as the wild type receptor [29]. This suggested that unlike the interaction between FcγRIIB and immune complex, internalisation of antibody-ligated CD20 was not mediated via FcγR-dependent signal transduction, implying that the role of FcγRIIB was restricted to physical/structural interactions.…”
Section: Mechanisms Of Internalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments were cleared through local ethical committee and performed under Home Office licenses PPL30/2451 and PPL30/2964. Ramos cells expressing hFcgRIIA or B were produced previously (24). Freestyle 293F cells were purchased from Invitrogen, Life Technologies (Inchinnan, Renfrewshire, U.K.).…”
Section: Animals and Cellsmentioning
confidence: 99%
“…Briefly, FcgR were amplified from cDNA obtained from primary human leukocytes (24) or C57BL/6 splenocytes using specific primers. For FcgR/rCD4 fusion proteins, FcgR extracellular domains were cloned into the pCD4 II vector N-terminal to rCD4 domains 3 and 4 to form soluble fusion constructs (25) before being digested and ligated into the pcDNA3.1 expression vector (Invitrogen, Life Technologies).…”
Section: Fcgr Abs and Reagentsmentioning
confidence: 99%